2014
DOI: 10.1002/fsn3.167
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant activity of various Mauritanian date palm (Phoenix dactylifera L.) fruits at two edible ripening stages

Abstract: The increasing interest in plant phenolics and flavonoids outlined the necessity of determining their contents and biological activity in Mauritanian date palm fruits. Methanolic extracts of fruit of six date palm cultivars commonly grown in Mauritania were screened for their antioxidant activity, total phenolics, and flavonoid content at two edible ripening stages. Polyphenols and flavonoids were higher in theBlah stage, corresponding toKhalal in the standard Iraqi Arabic nomenclature, compared to the fully m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
1

Year Published

2019
2019
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(25 citation statements)
references
References 27 publications
1
17
1
Order By: Relevance
“…Antioxidant activity of fruit pulp methanolic extracts was estimated using the 2,2-diphenyl-1pyrrylhydrazyl (DPPH) free radical assay as described by Brand-Williams et al [54] and Mint Mohamed Lemine et al [55]. The Absorbance was measured at 517 nm.…”
Section: Antioxidant Activity Of Fruit Pulpmentioning
confidence: 99%
“…Antioxidant activity of fruit pulp methanolic extracts was estimated using the 2,2-diphenyl-1pyrrylhydrazyl (DPPH) free radical assay as described by Brand-Williams et al [54] and Mint Mohamed Lemine et al [55]. The Absorbance was measured at 517 nm.…”
Section: Antioxidant Activity Of Fruit Pulpmentioning
confidence: 99%
“…(2014). [16] The results showed that polyphenols and flavonoids were higher in the Blah stage compared to those in the fully mature Tamr stage from all cultivars, with average total phenolics at the Blah and Tamr stages being 728.5 and 558.9 mg gallic acid equivalents (GAE)/100 g of dry matter, respectively, and average flavonoid content of 119.6 and 67.3 mg quercetin equivalents/100 g of dry matter, respectively. The Blah stage also had the highest total antioxidant activity, followed by Tijib, and a higher positive correlation was observed for total phenolics in both Tamr and Blah stages and antioxidant activities, compared to the flavonoids.…”
Section: Studies Based On Geographical Origin Of Date Fruitsmentioning
confidence: 99%
“…The Blah stage also had the highest total antioxidant activity, followed by Tijib, and a higher positive correlation was observed for total phenolics in both Tamr and Blah stages and antioxidant activities, compared to the flavonoids. [16]…”
Section: Studies Based On Geographical Origin Of Date Fruitsmentioning
confidence: 99%
“…The maturity stage is an important factor that may influence the compositional quality of the fruit [14,15]. During fruit ripening, several biochemical, physiological, and structural modifications occur and consequently influence the fruit quality [14][15][16]. Fat content of ripe and overripe fruit was 8.58% and 0.56%, respectively (Table 1).…”
Section: Nutritional Value As a Food Resourcementioning
confidence: 99%
“…Hence, it could be potentially used for the production of bioethanol similar to that of W. robusta in which bioethanol yield was found to be 71.42 AE 1.4 g ethanol/kg fruit [19]. [16]. Reduction in total phenolics, flavonoids, and condensed tannins occurs during maturation from the Khalal to Tamer stages, with the highest content at the Khalal stage [14].…”
Section: Nutritional Value As a Food Resourcementioning
confidence: 99%